PERAN PENEGAK HUKUM DALAM TINDAK MENANGGULANGI PIDANA DI BIDANG PERTANAHAN - Enni Merita (Justici, 2023)
ABSTRACT Crimes or criminal violations in land law, can be in the form of crimes and violations in the creation of physical data and juridical data, for example destroying land boundary markers and changing them to another place, providing false data or false information relating to the existence of land. This study uses a normative approach, normative juridical review. The type of research used is normative legal research that examines written law from various aspects, namely aspects of theory, philosophy, comparison, structure and composition, scope and material, consistency, general explanation, and article by article. very important in law enforcement of land crimes is the factor of legislation because if the law is very firm in giving sanctions to perpetrators of land crimes, the community will be afraid to commit violations and land crimes.